Humic acids reduce the addition of NPK and improve the quality of mango - García-Santiago, Juana Cruz; González-Fuentes, José Antonio; Rojas-Duarte, Alfonso; Hernández-Pérez, Armando; Aureoles-Rodríguez, Fabiola; Martínez-Mares, Regina (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of this study was to demonstrate that humic acids (AH) reduce the use of chemical fertilizers and increase the quality of mango cv. Ataulfo. A completely randomized design with a 3x2 factorial arrangement was used. The evaluated treatments were three doses of NPK (70, 100 and 130%) and two doses of AH (70 and 100 g plant−1 ). The results showed that when applying 70% NPK in combination with 100 g plant−1 of AH, a significant difference was obtained in the highest fresh weight and polar diameter of the fruit; while, when adding 130% of NPK with 70 g plant−1 of AH, the highest content of total soluble solids and titratable acidity was achieved; while the highest content of vitamin C in the fruits was reached when applying 100% NPK with 100 g plant−1 of AH.